Participatory Groups in Urban Flooding: The Case of Mandaue City, Cebu, Philippines - Montebon, Richie; Amparado, Mauro Allan; Son, Anna Liza (JPAIR Multidisciplinary Research, 2025)
Flooding affects people globally. Flooding leads to the loss of infrastructure, livelihood, essential belongings, and even lives. This study described the participatory groups created in the community for flooding and how men, women, and the LGBTQ community involved themselves in the participatory groups. This study is part of the Research Project "Exploring gendered knowledge and inclusiveness in community resilience for flooding disaster: Case studies in Can Tho City (Vietnam) and Metro Cebu (Philippines) funded by the Asia-Pacific Network for Global Climate Research, Kobe, Japan. A descriptive, exploratory, qualitative research endeavor was used in this study to look into the floods that affected the communities of Village Looc and Village Paknaan in Mandaue City, Cebu, Philippines. Twenty informants, comprising males, females, and LGBTQ community members from each village, participated in Focus Group Discussions (FGDs). All informants had resided in their respective villages for over a decade and possessed direct experience with local flooding events. Data collection involved in-depth interviews during the FGDs, followed by systematic data collation and analysis. The study revealed several key themes regarding community responses to flooding, and the study found that sexual orientation and gender identity expression do not impede one's ability to contribute effectively during crises. These findings underscore the importance of inclusive and well-structured emergency management strategies in mitigating the impact of disasters.
Keywords: Participatory Groups; Flood; Disaster Risk; Reduction and Management; Butuanon River Watershed; Water Quality Management Area; Mandaue City; Cebu; Philippines